Nano-selenium and its nanomedicine applications: a critical review - Hosnedlova, Bozena; Kepinska, Marta; Skalickova, Sylvie; Fernandez, Carlos; Ruttkay-Nedecky, Branislav; Peng, Qiuming; Baron, Mojmir; Melcova, Magdalena; Opatrilova, Radka; Zidkova, Jarmila; Bjørklund, Geir; Sochor, Jiri; et al. (International journal of nanomedicine, 2018)
Traditional supplements of selenium generally have a low degree of absorption and increased toxicity. Therefore, it is imperative to develop innovative systems as transporters of selenium compounds, which would raise the bioavailability of this element and allow its controlled release in the organism. Nanoscale selenium has attracted a great interest as a food additive especially in individuals with selenium deficiency, but also as a therapeutic agent without significant side effects in medicine. This review is focused on the incorporation of nanotechnological applications, in particular exploring the possibilities of a more effective way of administration, especially in selenium-deficient organisms. In addition, this review summarizes the survey of knowledge on selenium nanoparticles, their biological effects in the organism, advantages, absorption mechanisms, and nanotechnological applications for peroral administration.
Keywords: Nanoparticles; Nanomedicine; nanotechnologie; biomedicine; aplikace orální; lékové transportní systémy; Intestinal Mucosa; Nanotechnology; selen; nanoparticles; oxidative stress; Humans; protective effect; potravinářské přísady; anticancer effect; drug delivery; nanomedicína; nanočástice; střevní sliznice; Selenium; Administration, Oral; antimicrobial activity; Drug Delivery Systems; Food Additives; lidé